In vitro transcriptome analysis of porcine choroid plexus epithelial cells in response to Streptococcus suis: release of pro-inflammatory cytokines and chemokines - Schwerk, Christian; Adam, Rüdiger; Borkowski, Julia; Rudolph, Henriette; Klenk, Michael; Zink, Sascha; Bechtoldt, Natascha; Schmidt, Nicole; Stump-Guthier, Carolin; Sagar, Anubha; Spellerberg, Barbara; Tenenbaum, Tobias; et al. (Microbes and infection, 2011)
The Gram-positive zoonotic bacterium Streptococcus suis (S. suis) is responsible for a wide range of diseases including meningitis in pigs and humans. The blood-cerebrospinal fluid (CSF) barrier is constituted by the epithelial cells of the choroid plexus, which execute barrier function also after bacteria have entered the central nervous system (CNS). We show that the bacterial capsule, a major virulence factor, strongly attenuates adhesion of S. suis to the apical side of porcine choroid plexus epithelial cells (PCPEC). Oligonucleotide microarray analysis and quantitative PCR surprisingly demonstrated that adherent wild-type and capsule-deficient S. suis influenced expression of a pronounced similar pattern of genes in PCPEC. Investigation of purified capsular material provided no evidence for a significant role of the capsule. Enriched among the regulated genes were those involved in “inflammatory response”, “defense response” and “cytokine activity”. These comprised several cytokines and chemokines including the interleukins 6 and 8, which could be detected on protein level. We show that after infection with S. suis the choroid plexus contributes to the immune response by actively producing cytokines and chemokines. Other virulence factors than the bacterial capsule may be relevant in inducing a strong inflammatory response in the CNS during S. suis meningitis.
Gesehen am 31.10.2022
Available online 12 June 2011